Dimension X. - Asimov, Isaac, 1920-1992; Piper, H. Beam (Audio Archives, 1970)
The first story is about an archeologist who is ridiculed for suggesting that human life in the galaxy first evolved on the despised, radioactive planet, Earth. On side two, a man who is seriously wounded in World War Three returns briefly to his boyhood during World War Two bringing knowledge of the future.